2019
DOI: 10.21714/1984-3925_2019v22n2a4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory mechanisms on dishonesty of groups and individuals

Abstract: Objective: the purpose of this study is to present how the insertion of control mechanisms, such as auditing and professional ethical standards, would influence the dishonest behavior of individuals in particular, and within a group. Method: an experiment was performed with 204 participants in whom they would watch a die-rolling game and report the number shown by the dice. Nevertheless, the payment was tied to the number they reported and not to the number seen, thus making them dishonest. Originality/Relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
5
0
3
Order By: Relevance
“…a Kocher et al (2018) a Bonfim (2018) a Bonfim and Silva (2018) a Bonfim and Silva (2019) a Castillo et al (2020) 9 663 266 798 9 Each participant completes a matrix task individually in which they need to solve as many puzzles correctly as possible. Individuals then count how many puzzles they solved, shred the test sheet, and write down the number of solved puzzles on a collection slip.…”
Section: The Current Meta-analysismentioning
confidence: 99%
“…a Kocher et al (2018) a Bonfim (2018) a Bonfim and Silva (2018) a Bonfim and Silva (2019) a Castillo et al (2020) 9 663 266 798 9 Each participant completes a matrix task individually in which they need to solve as many puzzles correctly as possible. Individuals then count how many puzzles they solved, shred the test sheet, and write down the number of solved puzzles on a collection slip.…”
Section: The Current Meta-analysismentioning
confidence: 99%
“…Esse cenário é especialmente desafiador quando contrastado com dois aspectos relevantes e mutuamente dependentes que afetam o processo contábil: o primeiro diz respeito a discricionariedade que os gestores possuem nas tomadas de decisões (Seeger & Ulmer, 2003), que juntamente com a subjetividade das escolhas contábeis, sobretudo, a partir das normas internacionais, torna o papel dos gatekeepers mais relevante na análise de todo o ciclo de elaboração das informações contábeis, dado que estas devem ser cotejadas não somente sob a ótica da técnica empregada, mas também do comprometimento ético existente nas organizações de modo a mitigar o efeito de um comportamento desonesto (Bonfim & Silva, 2019).…”
Section: Análise Dos Dados E Resultadosunclassified
“…Os resultados possuem repercussões práticas em relação a atenção que deve pelas organizações ao tratarem das questões éticas e o processo de reconhecimento, mensuração e evidenciação das informações contábeis, pois à medida há um ambiente organizacional que possua falhas na conduta esperada de seus colaboradores (Bonfim & Silva, 2019;Kiradoo, 2020), inclusive aqueles envolvidos na área contábil, abre-se espaço para o cometimento de ações que reduzem a transparência dos relatórios contábeis e pelo aumento do gerenciamento de resultados.…”
Section: Asaaunclassified
“…Cost–benefit analyses indicate that punishment can influence dishonest behavior (Mazar & Ariely, 2006) and particularly reduce it (e.g., Bonfim & Silva, 2019; Chirikov et al, 2020; Peer & Feldman, 2021). For example, Bonfim and Silva (2019) found that informing groups that their reported die rolls might be subject to an audit, which would reduce their earnings to zero if caught cheating, reduced dishonesty from 27% to 9%. Similarly, Peer and Feldman (2021) studied the effect of fines and honesty oaths on dishonest behavior.…”
Section: Commitmentmentioning
confidence: 99%